Development Powtoon Animation Video in Indonesian Language Learning to Improve Student Learning Outcomes Elementary Schools - Renni Ramadhani Lubis; Siti Irene Astuti Dwiningrum; Enny Zubaidah (Universitas Muhammadiyah Sumatera Utara, Indonesia, 2023)
This study aims to develop powtoon based animated video media. This research is research and development (Research and Development). The models are defining stage, design stage, develop stage, and disseminate stage. But in this study only up to the develop stage. The research was conducted at SD Negeri 050660 Kwala Bingai. The research subjects were 25 students of class V, consisting of 13 male students and 12 female students. The object in this study is a powtoon based animated video. Data collection techniques are observation, questionnaires, and tests. Based on the feasibility results by linguists with a percentage of 89.55% it is categorized as feasible, media experts with a percentage of 90.25% are categorized as very feasible, and material experts with a percentage of 93.80% are categorized as very feasible. Based on the trials that have been carried out, it is known that the results of the pretest trial with a percentage of 36% with students who did not complete as many as 22 people. Meanwhile, the results of the posttest trial with a percentage of 88% with 24 students who completed. From the results of the feasibility and effectiveness of powtoon based animated videos in Indonesian language learning for fifth grade students at SD Negeri 050660 Kwala Bingai it is said that it is feasible and effective to use.